The Road to the blend of Augmented Reality and Intellectual Capital : a Case of Data Management for Outdoor Mobile Augmented Reality - Muhd Sadique, M.K; Khan, R.U.; Weng, E.N.; Zaidi Adruce, S. A. (Interdisciplinary Journal of Contemporary Reseaarch in Business, 2011)
Augmented reality (AR) presents a particularly powerful user interface (UI) to context-aware computing environments in a Knowledge-based economy. AR systems integrate virtual information/intellectual capital into a person's physical environment so that he or she will perceive that information as existing in their surroundings. In a limited mobile platform we propose a framework which covers the main problems of limited resources in mobile, server dependency for data management, processing and network latency, for outdoor mobile augmented reality. This model will be a gateway to explore and apply augmented reality and intellectual capital in future with full spirit.